Ketoprak Dor: Jejak Para Kuli Kontrak di Deli Serdang hingga Aceh Tengah - Susandro, Susandro (Creativity And Research Theatre Journal, 2023)
This article explores how contract laborers in Deli, North Sumatra, amidst the repression they received, played a role in developing the Mataraman ketoprak art into a new style of ketoprak called ketoprak dor, a staging style that was born by accident or without planning. Nevertheless, this art was still favored by overseas Javanese contract laborers until the performance was held in the village of Paya Tumpi, Central Aceh, marked by the emergence of several ketoprak dor groups there. This paper also describes how the form of ketoprak dor is in the two regions so that the differences or similarities in the staging styles can be read. This research approach is qualitative with descriptive analysis method. The techniques applied are in-depth interviews, literature studies, observation, documentation (videos, photos/pictures, audio during interviews), video searches on various YouTube accounts and other sources deemed relevant. The results obtained are ketoprak dor in Central Aceh originating from Deli, North Sumatra. The development of the Mataraman ketoprak art into ketoprak dor clearly took place there due to the limited transportation capacity that existed during the Dutch colonial period. This lack of power has encouraged contract workers to play ketoprak bang with makeshift musical instruments. Meanwhile, the existence of ketoprak dor in Central Aceh was encouraged by the existence of the Ketoprak Dor art group from Deli performing in Central Aceh, to be precise in Bies District in the decade of the 1950s. Another view is that Medan people moved to Bies and brought some Ketoprak Dor musical instruments and wanted to sell them when they got there. Because none of the Bies residents were able to redeem them, the Paya Tumpi residents agreed to this and the Ketoprak Dor arts group was formed named Sanggar Ketoprak Rahayu Cipto Rukun in the following decadeKeywords: Ketoprak Dor; Traces Of Contract Laborers ABSTRAKArtikel ini mengemukakan bagaimana para kuli kontrak di Deli, Sumatra Utara, di tengah represi yang diterima turut berperan mengembangkan kesenian ketoprak Mataram-an menjadi ketoprak gaya baru yang disebut ketoprak dor, suatu gaya pementasan yang lahir dari ketidaksengajaan atau tanpa direncanakan. Kendati demikian, kesenian tersebut tetap saja disukai oleh para kuli kontrak beretnis Jawa perantauan hingga pertunjukannya digelar di gampong (kampung) Paya Tumpi, Aceh Tengah, ditandai dengan bermunculannya beberapa grup ketoprak dor di sana. Tulisan ini juga mendeskripsikan bagaimana bentuk kesenian ketoprak dor di kedua wilayah tersebut sehingga dapat terbaca perbedaan atau persamaan gaya pementasannya. Pendekatan penelitian ini ialah kualitatif dengan metode analisis deskriptif. Teknik yang diterapkan ialah wawancara mendalam, studi kepustakaan, observasi, dokumentasi (video, foto/gambar, audio saat wawancara), penelusuran video di berbagai akun youtube dan sumber lainnya yang dianggap relevan. Hasil yang didapat ialah ketoprak dor yang ada di Aceh Tengah berasal dari Deli, Sumatra Utara. Perkembangan kesenian ketoprak Mataraman menjadi ketoprak dor jelas terjadi di sana bersebab keterbatasan daya transportasi yang ada di masa kolonial Belanda. Minimnya daya tersebut mendorong para kuli kontrak untuk bermain ketoprak dor dengan alat musik yang seadanya. Sedangkan keberadaan ketoprak dor di Aceh Tengah didorong adanya kelompok kesenian Ketoprak Dor asal Deli berpentas ke Aceh Tengah, tepatnya di Kecamatan Bies di kisaran dekade 50-an. Pandangan lainnya ialah adanya orang Medan yang pindah ke Bies sekaligus membawa beberapa alat musik Ketoprak Dor lalu ingin menjualnya sesampai di sana. Karena warga Bies tidak ada yang mampu menebus, maka warga Paya Tumpi menyanggupinya hingga terbentuklah kelompok kesenian Ketoprak Dor bernama Sanggar Ketoprak Rahayu Cipto Rukun pada dekade berikutnyaKata Kunci : Ketoprak Dor; Jejak Kuli Kontrak